2001
DOI: 10.1128/jb.183.19.5659-5667.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Functional Domains of the Enterococcus faecalis Pheromone-Induced Surface Protein Aggregation Substance

Abstract: Pheromone-inducible aggregation substance (AS) proteins of Enterococcus faecalis are essential for highefficiency conjugation of the sex pheromone plasmids and also serve as virulence factors during host infection. A number of different functions have been attributed to AS in addition to bacterial cell aggregation, including adhesion to host cells, adhesion to fibrin, increased cell surface hydrophobicity, resistance to killing by polymorphonuclear leukocytes and macrophages, and increased vegetation size in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 37 publications
5
76
0
3
Order By: Relevance
“…However, parallels to the Ti plasmids appear to exist, insofar as many of the components of the pheromone-mediated conjugation system also seem to be involved in host-parasite interactions of enterococci (95,217,226). Hirt et al (95) demonstrated that E. faecalis cells harboring pCF10 showed significantly increased virulence in a rabbit endocarditis model.…”
Section: Sex Pheromone Plasmidsmentioning
confidence: 99%
“…However, parallels to the Ti plasmids appear to exist, insofar as many of the components of the pheromone-mediated conjugation system also seem to be involved in host-parasite interactions of enterococci (95,217,226). Hirt et al (95) demonstrated that E. faecalis cells harboring pCF10 showed significantly increased virulence in a rabbit endocarditis model.…”
Section: Sex Pheromone Plasmidsmentioning
confidence: 99%
“…PrgB is a large ϳ137-kDa protein with homologs identified primarily in related pheromone-inducible conjugative plasmids in en- terococci. In addition to an N-terminal signal sequence and C-terminal LPXTG cell wall anchor motif, PrgB contains internal RGD motifs and aggregation domains shown to be important for the binding of lipoteichoic acid, adherence to eukaryotic cells, and bacterial internalization by epithelial cells (see below) (65,67,221,266,284,285,286). prgB mutants show reductions in pCF10 transfer efficiencies by several orders of magnitude, although transfer still occurs on solid surfaces.…”
Section: Gram-positive T4ssmentioning
confidence: 99%
“…Once recipient cells acquire pX, they start to produce a pheromone inhibitor (iX) to block the activity of cX and to prevent selfclumping of donor cells (7,20,23). If plasmid-free cells secreting cX get close to donor cells, the cX outcompetes iX and triggers the mating processes including the synthesis of a surface adhesin, so-called "aggregation substance" (AS) (13,14,15,16,39). AS expressed on the surface of donor cells leads to binding to recipient cells and induces mating aggregates in which the plasmid is transferred at high frequency.…”
mentioning
confidence: 99%